Kontinuitas tradisi breast ironing dalam komunitas imigran Kamerun di Inggris - Simangunsong, Rahayu A. H. (Institute for Advanced Science, Social, and Sustainable Future, 2024)
The practice of breast ironing is one of many traditions in the world whose practice is based on the mindset that women's sexuality is something that must be controlled. This paper is intended to answer the question that is central to the author's research, namely: